Anxiety about Speaking a Foreign Language as a Mediator of the Relation between Motivation and Willingness to Communicate. Issue 3 (December 2014) - Wu, Chia-Pei; Lin, Huey-Ju
The purpose of this study was to examine whether anxiety about speaking a foreign language mediated the relation between motivation and a willingness to communicate among 107 Taiwanese students sampled from two public universities and one private university. A regression analysis indicated that motivation was negatively related to university students' anxiety about speaking a foreign language and positively related to willingness to communicate. Furthermore, anxiety about speaking a foreign language was negatively related to university students' willingness to communicate, and also partially mediated the relationship between motivation and willingness to communicate. The findings suggest that high motivation and low anxiety about speaking a foreign language are needed for Taiwanese students to demonstrate a stronger willingness to communicate.